Utilizing Outpatient Pelvic Reconstructive Surgery in the Era of the COVID-19 Pandemic. Issue 12 (December 2021) - Berger, Alexander A.; Tan-Kim, Jasmine; Menefee, Shawn A.
Abstract : Objective: The COVID-19 pandemic has created a significant strain on the medical system, creating resource scarcity. We sought to demonstrate the reduction in hospital room utilization after implementation of outpatient pelvic reconstructive surgery. Methods: We included all minimally invasive reconstructive surgical procedures in this retrospective cohort study within a large managed care organization of 4.5 million members (2008–2018). We queried the system-wide medical record for Current Procedural Terminology (CPT), International Classification of Diseases, Ninth Revision (ICD-9), and International Classification of Diseases, Tenth Revision (ICD-10) codes for all included procedures and patient perioperative data. Categorical variables were compared using χ 2 test for categorical variables and the Kruskal-Wallis test for continuous variables. Results: Of the 13, 445 patients undergoing pelvic reconstructive surgery, 5, 506 were discharged the same day, whereas 7, 939 were discharged the next day. Over the 10-year period, patients without hysterectomy had outpatient surgery rates increase from 31.2% to 76.4% (+45.2%), whereas those with hysterectomy increased from 3% to 56.4% (+53.4%). Hospital room utilization decreased by 45, 200 room days/100, 000 reconstructive procedures without hysterectomy and 53, 400 room days/100, 000 reconstructive procedures with hysterectomy. When compared to 2008, in 2018 after more widespread adoption of outpatient elective surgery, for the 738 patients undergoing surgery without hysterectomy, 334 less room days were used, whereas 335 less room days were used among the 640 patients who had a surgical procedure with hysterectomy. Conclusions: The implementation of outpatient pelvic reconstructive procedures leads to a significant reduction in hospital room utilization. Same-day discharge decreases hospital resource utilization, therefore improving hospital access, which may be essential for the delivery of routine care during times of resource scarcity such as the COVID-19 pandemic.